Internationalization of portuguese firms: motivations, cultural influence and entry modes - Cruz, André G.B. Pereira da (2014)
This thesis is part of the Master of Science in Business Administration. Writing about the Portuguese firm’s internationalization allows a greater understanding of good practices among these companies as well as being able to make suggestions to further improve internationalization processes. After providing theoretical frameworks and theories on International Business, five successful Portuguese companies were analyzed and then compared with the existing literature. In general terms, it was concluded that Internationalization may be of major importance for a firm’s growth and that motivational factors as well as the cultural understanding abilities are linked to international success. The research done also proved that the choice of an entry mode does not determine the success of an Internationalization strategy, instead a quality networking and the international commitment the firm intends to achieve will influence and allow the firm to use the selected entry mode successfully.